A Systematic Review of the Root Canal Microbiota Associated with Apical Periodontitis: Lessons from Next‐Generation Sequencing - Manoil, Daniel; Al‐Manei, Khaled; Belibasakis, Georgios N. (Proteomics. Clinical applications, 2020)
Next‐generation sequencing (NGS) has now been applied for a decade to characterize the microbiota composition of infected dental root canals associated with apical periodontitis. Here, the study aims at systematically and critically reviewing these reports within the outcome of interest selected; the microbiota composition in different endodontic infection types. Standard methodological guidelines as stated by the PRISMA and the Joanna Briggs Institute are followed, including a risk of bias assessment. A literature search is conducted using the PubMed Advanced‐Search Builder on April 8, 2019; only original research articles that investigated the microbiota of infected root‐canals by means of NGS are screened. Among the 26 articles initially identified, 18 are included and evaluated for the following parameters; sampling protocol, sequencing strategy, and microbiota composition. The endodontic infections include primary apical periodontitis (PAP), secondary apical periodontitis (SAP), and apical abscess (AA). All infection types are associated with a highly diverse microbiota. Although some taxa appear differentially abundant between PAPs, SAPs, and AAs, no evident clustering of the microbiota by infection type is observed. These studies collectively formulate a comprehensive map of the taxa associated with endodontic infections and provide evidence of compositionally unspecific, yet abundance differentiates, community profiles according to clinical diagnosis.